2021
DOI: 10.3390/cells10082124
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic Stimulation Synchronizes a Broad Spectrum of Action Potential Firing Rates of Cardiac Pacemaker Cells toward a Higher Population Average

Abstract: The heartbeat is initiated by pacemaker cells residing in the sinoatrial node (SAN). SAN cells generate spontaneous action potentials (APs), i.e., normal automaticity. The sympathetic nervous system increases the heart rate commensurate with the cardiac output demand via stimulation of SAN β-adrenergic receptors (βAR). While SAN cells reportedly represent a highly heterogeneous cell population, the current dogma is that, in response to βAR stimulation, all cells increase their spontaneous AP firing rate in a s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 70 publications
2
13
0
Order By: Relevance
“…A substantial cell-to-cell variability in phospholamban phosphorylation is expected based on a substantial variability of both basal AP firing rates and responses to β-adrenergic stimulation among isolated SAN cells ( Kim et al, 2021 ). However, in contrast to g CaL , there is no single-cell data in the literature to set up cell populations in the model within an exact P up range.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial cell-to-cell variability in phospholamban phosphorylation is expected based on a substantial variability of both basal AP firing rates and responses to β-adrenergic stimulation among isolated SAN cells ( Kim et al, 2021 ). However, in contrast to g CaL , there is no single-cell data in the literature to set up cell populations in the model within an exact P up range.…”
Section: Resultsmentioning
confidence: 99%
“…This results in a large degree of functional heterogeneity among individual cells, ranging from frequently and rhythmic AP firing to infrequently and dysrhythmic firing, to nonfiring cells (recently dubbed “dormant” cells) ( Kim et al, 2018 ; Tsutsui et al, 2018 ; Tsutsui et al, 2021 ). The SAN cell population is also extremely heterogeneous with respect to the AP firing rate increase in response to β-adrenergic stimulation ( Kim et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, SANC with different ion channel expression span the whole SAN and represent a reserve pool of SANC capable of reaching normal frequency upon multiple external stimuli, ensuring SAN adaptability. Indeed, a recent study showed that all SANC with various basal rates tend to reach the same frequency under β-adrenergic stimulation [ 23 ]. In this regard, our data indicate that in dormant SANC, Ca v 1.3 channels are essential to reach this synchronized average rate among SANC during the fight-or-flight response.…”
Section: Discussionmentioning
confidence: 99%
“…This β-adrenergic effect was also observed in isolated dormant human SANC [ 22 ]. Interestingly, a recent study showed that the chronotropic response is actually different among SANC with various basal firing rates which results, ultimately, in a synchronized average rate for all SANC under β-adrenergic stimulation [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the many insights obtained by these studies, important questions remain unresolved, particularly with respect to how heterogeneity between SAN myocytes and inter-cellular coupling combine to influence coordinated beating in tissue. For example, although it has recently been shown experimentally that not all SAN cells fire spontaneously when they are enzymatically isolated [8][9][10], we do not know how non-firing cells behave when they are electrically coupled in tissue, nor how the percentage of non-firing cells influences the overall electrical activity of the SAN.…”
Section: Introductionmentioning
confidence: 99%